Anti-adhesion smooth nylon master batch as well as preparation method and application thereof

By using a combination masterbatch of inorganic powder, surface treatment agent and nylon resin in nylon film, the problem of adhesion of nylon film is solved, and good dispersion performance and anti-adhesion effect are achieved. It is suitable for the production of high-transparent nylon films, improving the Production efficiency and film performance.

CN119119721APending Publication Date: 2024-12-13FSPG HI TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411172810.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The lack of anti-adhesion masterbatch suitable for nylon films in the prior art leads to prone to adhesion during the production process, affecting high-speed line production, and the differences in physical and chemical properties between the anti-adhesion agent and the plastic particles lead to poor mixing and dispersion effect. , affects the performance of the film.

Method used

The nylon masterbatch including inorganic powder, surface treatment agent and nylon resin is prepared by stirring and melt extrusion processes. The surface treatment agent is used to reduce the surface energy of the inorganic powder and achieve good mixing in nylon polymers. and bond to form fine concave and bumps to prevent adhesion, while controlling the proportion of raw materials to ensure the optical and dispersive properties of the film.

Benefits of technology

It realizes the anti-adhesion effect of nylon film, reduces the mesh pressure and the number of film ruptures, maintains the optical performance and wetting tension of the film, and is suitable for the production of high-transparent nylon films and nylon substrate films for high-speed packaging, improving production Efficiency and reduce manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005009811540000071
    Figure BDA0005009811540000071
  • Figure BDA0005009811540000081
    Figure BDA0005009811540000081
Patent Text Reader

Abstract

The invention belongs to the technical field of thin film materials, and discloses an anti-adhesion and smooth nylon master batch as well as a preparation method and application thereof. The nylon master batch is prepared from the following raw materials: inorganic powder, a surface treating agent and nylon resin, the inorganic powder comprises silicon dioxide and / or glass beads, and the surface treating agent comprises fatty acid amide, (carboxyl decyl) terminated-polydimethylsiloxane and hexamethylenediamine. The nylon master batch provided by the invention also has the advantages of low net passing pressure, less film breaking times, no precipitation and the like caused by excellent dispersing performance on the basis of preventing the adhesion of the nylon film, and is particularly suitable for production of high-transparency nylon films, nylon base material films for high-speed packaging, especially nylon packaging films for shallow printing; and the influence on film transparency, corona treatment and printing composition is little.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of film materials, and particularly relates to an anti-adhesion and smooth nylon masterbatch and a preparation method and application thereof. Background Art

[0002] Anti-adhesive agents are usually added in the production of films, otherwise there will be many problems in the winding, slitting and other processes of the film production process and in the subsequent packaging and use, and even the film cannot be used. In particular, modern plastic processing is developing towards automation, high speed and high quality. The faster the processing speed, the easier it is to generate static electricity due to friction, and the easier it is for the films to stick together, which seriously hinders high-speed line production. In addition, the better the transparency of the film and the higher the processing temperature, the easier it is to stick together. Therefore, anti-adhesive agents play an extremely important role both in the manufacturing process of the film product itself and in the automated packaging process used later. In this sense, anti-adhesive agents are the most important additives in film production. Anti-adhesion agents are generally fine inorganic powder materials, such as natural diatomaceous earth, calcium carbonate, synthetic silica, etc., with an average particle size of 1-5μm. They are added to the surface of the film to form tiny concave and convex points. On the one hand, this weakens the vacuum between the two films, and on the other hand, countless entanglement weaknesses are formed between the concave and convex points, thereby playing an anti-adhesion effect. Usually, the effective addition amount in the surface of the film is 500-5000ppm. However, due to the large difference in physical and chemical properties between inorganic powder materials and plastic particles, it is difficult to obtain an ideal mixing and dispersion effect if they are directly added to the molded film products, which has many negative effects on the film performance, and it is easy to accumulate dust, which is not conducive to the manufacturing environment of the film. Therefore, it is necessary to pre-form a plastic particle (masterbatch) with a high content of concentrated anti-adhesion agent, and then add it to the film in the form of a masterbatch.

[0003] At present, the anti-blocking masterbatches on the market mainly include two categories: anti-blocking masterbatches for PP films and anti-blocking masterbatches for PE films. They are not suitable for use in films mainly made of nylon, and there is no relevant research on anti-blocking masterbatches for nylon films. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides an anti-adhesion and smooth nylon masterbatch and its preparation method and application. The nylon masterbatch has the advantages of low screen pressure, less film breakage times, no precipitation, etc. due to its excellent dispersion performance, and is particularly suitable for the production of high-transparency nylon film, nylon substrate film for high-speed packaging, and especially nylon packaging film for shallow printing.

[0005] The first aspect of the present invention provides a nylon masterbatch, which includes the following preparation raw materials: inorganic powder, surface treatment agent and nylon resin; the inorganic powder includes silica and / or glass beads, and the surface treatment agent includes fatty acid amide, (carboxydecyl) end-capped polydimethylsiloxane and hexamethylenediamine.

[0006] Specifically, the nylon resin in the present invention serves as a carrier of other raw material additives, maintaining compatibility with the main material of the nylon film product to be prepared downstream; the inorganic powder, as the main effective component of the masterbatch, can form many fine concave and convex points on the surface of the film, which is conducive to the entry of air and reduces the entanglement of the macromolecular segments between the films, thereby preventing the film from sticking. At the same time, the inorganic powder has a fine size and a narrow particle size distribution (average particle size of 2-4μm, maximum particle size D98≤10μm), which can ensure the excellent optical properties of the film; the surface treatment agent has both organic long chain segments and active groups, can react with the polar groups on the inorganic powder, reduce its surface energy, prevent the fine inorganic powder particles from agglomerating, and achieve good mixing and bonding of the inorganic powder in the nylon high molecular polymer, playing a bridging role.

[0007] In some embodiments of the present invention, the nylon masterbatch is composed of the following raw materials, calculated by mass percentage: 2-10% inorganic powder, 1-20% surface treatment agent and the balance nylon resin.

[0008] In some embodiments of the present invention, the mass ratio of the (carboxydecyl)-terminated polydimethylsiloxane to hexamethylenediamine is (1-2): 1. If the (carboxydecyl)-terminated polydimethylsiloxane is excessive and the hexamethylenediamine is insufficient, the (carboxydecyl)-terminated polydimethylsiloxane will not be completely reacted, resulting in incomplete reaction, increased precipitation, and serious impact on the surface energy of the film, and significant attenuation of wetting tension. Therefore, for the raw materials containing siloxane components, it is particularly important to accurately control the ratio of each reaction raw material to achieve the best comprehensive performance.

[0009] In some embodiments of the present invention, the content of the fatty acid amide in the nylon masterbatch is 3-5 wt %.

[0010] In some embodiments of the present invention, the content of the (carboxydecyl)-terminated polydimethylsiloxane in the nylon masterbatch is 5-10 wt %.

[0011] In some embodiments of the present invention, the content of hexamethylenediamine in the nylon masterbatch is 3-5 wt %.

[0012] In some embodiments of the present invention, the inorganic powder is silicon dioxide, preferably gel-process silicon dioxide.

[0013] In some embodiments of the present invention, the nylon resin includes at least one of aliphatic nylon and copolymers thereof, semi-aromatic nylon and copolymers thereof, and aromatic nylon and copolymers thereof.

[0014] In some embodiments of the present invention, the nylon resin includes at least one of nylon 6, nylon 66, nylon 1010, nylon 1012, nylon 11 and nylon 12.

[0015] In some embodiments of the present invention, the fatty acid amide is a branched fatty acid amide.

[0016] In some embodiments of the present invention, the fatty acid amide comprises eicosamide.

[0017] In some embodiments of the present invention, the nylon masterbatch is in the form of translucent to light white small cylindrical or flake particles.

[0018] The second aspect of the present invention provides a method for preparing the nylon masterbatch according to the first aspect of the present invention, comprising the following steps:

[0019] The inorganic powder, the surface treatment agent and the nylon resin are mixed, stirred and melt-extruded to obtain the nylon masterbatch.

[0020] In some embodiments of the present invention, the stirring speed is 100-300r / min; and / or the stirring time is 1-10min. During the stirring and mixing process, the material will generate a certain amount of friction heat, which will promote the chemical grafting reaction between the surface treatment agent and the inorganic powder, and the inorganic powder will change from hydrophilic to semi-hydrophobic or fully hydrophobic, the surface energy will be greatly reduced, and the dispersibility will be increased, so that it will adhere to the nylon resin more evenly.

[0021] In some embodiments of the present invention, the melt extrusion adopts a twin-screw extruder; wherein the screw diameter is 30-80 mm, the aspect ratio is 35-50, the extruder temperature is 200-300°C, the die head temperature of the extruder is 230-270°C, the feeding rate is 10-60r / min, and the screw speed is 100-300r / min.

[0022] In some embodiments of the present invention, after the melt extrusion, water cooling and pelletizing steps are further included; the water flow length of the water cooling is ≤0.5m, and the rotation speed of the pelletizer used for the pelletizing is 100-300r / min.

[0023] The third aspect of the present invention provides the use of the nylon masterbatch described in the first aspect of the present invention in the preparation of nylon film.

[0024] According to a fourth aspect of the present invention, a nylon film is provided, wherein the raw materials for preparing the nylon film include the nylon masterbatch according to the first aspect of the present invention.

[0025] In some embodiments of the present invention, the nylon film includes a biaxially oriented nylon film (BOPA film), a cast nylon film, and a multi-layer co-extruded blown film with nylon as the surface layer.

[0026] In some embodiments of the present invention, the nylon film includes an upper surface layer, a middle layer and a lower surface layer, the upper surface layer or the lower surface layer is corona treated, and the raw material for preparing the surface layer that has not been corona treated includes the nylon masterbatch described in the first aspect of the present invention.

[0027] In some embodiments of the present invention, the mass of the nylon masterbatch described in the first aspect of the present invention accounts for 1-10% of the total mass of the raw materials for preparing the surface layer that has not been corona treated, preferably 3-7%, and more preferably 4-6%.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0029] (1) The nylon masterbatch of the present invention solves the problems of stickiness and film curling angle in the production process of nylon film, and has no adverse effect on other properties of the film, thereby ensuring the rapid and stable production of nylon film, improving production efficiency and reducing the overall manufacturing cost of the product.

[0030] (2) The nylon film made from the nylon masterbatch of the present invention has a small static / dynamic friction coefficient and a small haze; at the same time, the surface tension stability of the film is good, the corona value decays slowly, and it can maintain a high wetting tension after being stored for one month, avoiding affecting subsequent printing and other processes. DETAILED DESCRIPTION

[0031] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0032] Unless otherwise specified, the raw material components, reagents or devices used in the present invention can be obtained from conventional commercial channels or by existing known methods.

[0033] Example 1

[0034] The invention discloses an anti-adhesion and smooth nylon masterbatch, which is composed of the following raw materials: 5wt% of gel-process silica, 3wt% of eicosamide, 5wt% of (carboxyl decyl) end-capped polydimethylsiloxane, 3wt% of hexamethylenediamine and 84wt% of nylon 6.

[0035] The method for preparing the anti-adhesive and smooth nylon masterbatch in this example comprises the following steps:

[0036] (1) adding gel silica, eicosamide, (carboxydecyl)-terminated polydimethylsiloxane, hexamethylenediamine and nylon 6 into a high-speed mixer, stirring at a stirring speed of 200 r / min for 5 min to obtain a mixed material, and discharging the mixed material for later use;

[0037] (2) putting the mixed material obtained in step (1) into the hopper of a twin-screw extruder, starting the twin-screw extruder and starting feeding at the same time, wherein the screw diameter of the twin-screw extruder used is 60 mm, the aspect ratio is 45, the temperature of the extruder is 270° C., the die temperature of the extruder is 270° C., the feeding speed is 25 r / min, the screw speed is 100 r / min, the material is melted and extruded into strips through a porous die, and immediately enters cooling water for cooling, and the supercooling water length is 0.4 m;

[0038] (3) pelletizing and drying the material strips after cooling in step (2).

[0039] After testing, the relative viscosity of the nylon masterbatch prepared in this example was 3.05, the moisture content was 1450 ppm, and the ash content was 56800 ppm.

[0040] Example 2

[0041] The invention discloses an anti-adhesion and smooth nylon masterbatch, which is composed of the following raw materials: 5wt% of gel-process silica, 5wt% of eicosamide, 10wt% of (carboxyl decyl) end-capped polydimethylsiloxane, 5wt% of hexamethylenediamine and 75wt% of nylon 6.

[0042] The method for preparing the anti-adhesive and smooth nylon masterbatch in this example comprises the following steps:

[0043] (1) adding gel silica, eicosamide, (carboxydecyl)-terminated polydimethylsiloxane, hexamethylenediamine and nylon 6 into a high-speed mixer, stirring at a stirring speed of 200 r / min for 5 min to obtain a mixed material, and discharging the mixed material for later use;

[0044] (2) putting the mixed material obtained in step (1) into the hopper of a twin-screw extruder, starting the twin-screw extruder and starting feeding at the same time, wherein the screw diameter of the twin-screw extruder used is 60 mm, the aspect ratio is 45, the temperature of the extruder is 270° C., the die temperature of the extruder is 270° C., the feeding speed is 25 r / min, the screw speed is 100 r / min, the material is melted and extruded into strips through a porous die, and immediately enters cooling water for cooling, and the supercooling water length is 0.4 m;

[0045] (3) pelletizing and drying the material strips after cooling in step (2).

[0046] After testing, the relative viscosity of the nylon masterbatch prepared in this example was 3.01, the moisture content was 1270 ppm, and the ash content was 59700 ppm.

[0047] Example 3

[0048] The invention discloses an anti-adhesion and smooth nylon masterbatch, which is composed of the following raw materials: 5wt% of glass microbeads, 3wt% of eicosamide, 5wt% of (carboxyl decyl) end-capped polydimethylsiloxane, 3wt% of hexamethylenediamine and 84wt% of nylon 6.

[0049] The method for preparing the anti-adhesive and smooth nylon masterbatch in this example comprises the following steps:

[0050] (1) adding glass microspheres, eicosamide, (carboxydecyl)-terminated polydimethylsiloxane, hexamethylenediamine and nylon 6 into a high-speed mixer, stirring at a stirring speed of 200 r / min for 5 min to obtain a mixed material, which is then discharged for later use;

[0051] (2) putting the mixed material obtained in step (1) into the hopper of a twin-screw extruder, starting the twin-screw extruder and starting feeding at the same time, wherein the screw diameter of the twin-screw extruder used is 60 mm, the aspect ratio is 45, the temperature of the extruder is 270° C., the die temperature of the extruder is 270° C., the feeding speed is 25 r / min, the screw speed is 100 r / min, the material is melted and extruded into strips through a porous die, and immediately enters cooling water for cooling, and the supercooling water length is 0.4 m;

[0052] (3) pelletizing and drying the material strips after cooling in step (2).

[0053] After testing, the relative viscosity of the nylon masterbatch prepared in this example was 3.05, the moisture content was 1367 ppm, and the ash content was 59680 ppm.

[0054] Comparative Example 1 (the only difference from Example 1 is that no surface treatment agent is added)

[0055] A nylon masterbatch is composed of the following raw materials: 5wt% of gel-process silica and 95wt% of nylon 6.

[0056] The preparation method of nylon masterbatch in this example is prepared by referring to the preparation method in Example 1.

[0057] After testing, the relative viscosity of the nylon masterbatch prepared in this example was 3.08, the moisture content was 1500ppm, and the ash content was 20100ppm.

[0058] Comparative Example 2

[0059] The only difference from Example 1 is that the gel-process silicon dioxide is replaced by calcium carbonate in equal amount, and the other raw materials, amounts and preparation methods are the same as those in Example 1.

[0060] After testing, the relative viscosity of the nylon masterbatch prepared in this example was 3.03, the moisture content was 1753 ppm, and the ash content was 48790 ppm.

[0061] Comparative Example 3

[0062] The only difference from Example 1 is that an equal amount of eicosamide is replaced by oleamide, and the remaining raw materials, amounts and preparation method are the same as those in Example 1.

[0063] After testing, the relative viscosity of the nylon masterbatch prepared in this example was 3.11, the moisture content was 1490 ppm, and the ash content was 49800 ppm.

[0064] Comparative Example 4 (the only difference from Example 1 is that hexamethylenediamine is not added)

[0065] A nylon masterbatch is composed of the following raw materials: 5wt% of gel-process silica, 3wt% of eicosamide, 5wt% of (carboxyl decyl) end-capped polydimethylsiloxane and 87wt% of nylon 6.

[0066] The preparation method of nylon masterbatch in this example is prepared by referring to the preparation method in Example 1.

[0067] After testing, the relative viscosity of the nylon masterbatch prepared in this example was 3.09, the moisture content was 1566 ppm, and the ash content was 60231 ppm.

[0068] Product performance testing

[0069] The nylon masterbatch prepared in Examples 1-3 and Comparative Examples 1-4 was added to the non-corona treated layer of a 15 μm thick three-layer BOPA film at an addition amount of 5 wt% (the BOPA film has an upper surface layer, a lower surface layer and an intermediate layer, the upper surface layer is corona treated, and the lower surface layer is not corona treated. The nylon masterbatch is added to the lower surface layer. If it migrates to the corona treated layer in the reverse direction, it will affect the corona attenuation); and the following tests were performed: the friction coefficient was in accordance with GB / T10006-2021, the haze was in accordance with GB / T2410-2008, the wetting tension was in accordance with GB / T14216-2008, and the melt pressure was the data automatically recorded by the production equipment. The test results are shown in Table 1.

[0070] Table 1

[0071]

[0072]

[0073] As shown in Table 1, compared with Example 1, Comparative Example 1 uses inorganic powder directly mixed with nylon resin carrier for granulation. Since it does not contain a surface treatment agent, it has little effect on the corona treatment value and can maintain a high wetting tension after one month. Although it is beneficial for printing and composite aluminum plating, it has a high haze and a large friction coefficient due to poor dispersion, and the film has poor slip and anti-adhesion performance. At the same time, the agglomerated particles cause the filter pressure to be high, and the processability is poor.

[0074] Comparative Example 2 uses calcium carbonate. Since calcium carbonate is a crystalline inorganic powder, it has a greater impact on the transparency of the film than amorphous silicon dioxide, and the haze will be larger.

[0075] Compared with the oleic acid amide used in Comparative Example 3, the branched eicosamide used in Example 1 does not contain unsaturated double bonds in its molecular structure, has better heat-resistant oxidation performance, is more suitable for the high-temperature processing state of nylon, has very little decomposition and volatilization, and has a relatively gentle and uniform precipitation rate. When migrating to the surface, the molecules are more firmly embedded in the surface of the nylon matrix through the branched structure, thereby reducing the frosting and peeling phenomenon during subsequent use, and no water-stained oil stains will appear. While retaining a good smooth effect, the surface tension of the film after corona treatment is well maintained, and in the subsequent printing, compounding and aluminum plating processes, it exhibits excellent characteristics of smooth running, excellent appearance, high compound strength, and exquisite printing;

[0076] Compared with the comparative example 4 without adding hexamethylenediamine, in the high-temperature molten state, the carboxyl group in the (carboxydecyl)-terminated polydimethylsiloxane in Example 1 undergoes an amidation reaction with the hexamethylenediamine in the system to form a copolymer reactant containing siloxane. This reactant also has a molecular segment structure similar to that of the nylon matrix itself, so that the dispersibility of the entire masterbatch compounding system and the compatibility of the nylon matrix are effectively improved, and the (carboxydecyl)-terminated polydimethylsiloxane can also react with the hydroxyl group on the surface of silica. The raw materials work together to achieve the optimal state. This quasi-interpenetrating network structure can firmly fix the siloxane component on the surface of the nylon film without slipping and precipitation. It is both anti-sticky and has the thermal smoothness of siloxane, and has little effect on the transparency of the film, corona treatment, and printing composite.

[0077] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A nylon masterbatch, It is characterized in that The nylon masterbatch comprises the following preparation raw materials: inorganic powder, surface treatment agent and nylon resin; the inorganic powder comprises silicon dioxide and / or glass microbeads, and the surface treatment agent comprises fatty acid amide, (carboxyl decyl) end-capped polydimethylsiloxane and hexamethylenediamine.

2. The nylon masterbatch according to claim 1, It is characterized in that Calculated by mass percentage, the nylon masterbatch is composed of the following raw materials: 2-10% of inorganic powder, 1-20% of surface treatment agent and the remainder of nylon resin.

3. The nylon masterbatch according to claim 1, It is characterized in that The mass ratio of the (carboxydecyl)-terminated polydimethylsiloxane to hexamethylenediamine is (1-2):

1.

4. The nylon masterbatch according to claim 1, It is characterized in that The nylon resin includes at least one of aliphatic nylon and copolymers thereof, semi-aromatic nylon and copolymers thereof, and aromatic nylon and copolymers thereof.

5. The nylon masterbatch according to claim 1, It is characterized in that The fatty acid amides include eicosamide.

6. A method for preparing a nylon masterbatch according to any one of claims 1 to 5, It is characterized in that The following steps are involved: The inorganic powder, the surface treatment agent and the nylon resin are mixed, stirred and melt-extruded to obtain the nylon masterbatch.

7. The preparation method according to claim 6, It is characterized in that The stirring speed is 100-300 r / min; and / or the stirring time is 1-10 min.

8. The preparation method according to claim 6, It is characterized in that The melt extrusion adopts a twin-screw extruder; wherein the screw diameter is 30-80mm, the aspect ratio is 35-50, the extruder temperature is 200-300°C, the die head temperature of the extruder is 230-270°C, the feeding speed is 10-60r / min, and the screw speed is 100-300r / min.

9. Use of the nylon masterbatch according to any one of claims 1 to 5 in the preparation of nylon film.

10. A nylon film, It is characterized in that The raw materials for preparing the nylon film include the nylon masterbatch according to any one of claims 1 to 5.

Citation Information

Cited By

  • Regenerated cellulose membrane for cigarette tipping paper and preparation method of regenerated cellulose membrane

    CN122502691A